Herpetopanone, a diterpene from Herpetosiphon aurantiacus discovered by isotope labeling - Pan, Xinli; Domin, Nicole; Schieferdecker, Sebastian; Kage, Hirokazu; Roth, Martin; Nett, Markus (Beilstein Journal of Organic Chemistry, 2017)
The genome of the predatory bacterium Herpetosiphon aurantiacus 114-95T harbors a number of biosynthesis genes, including four terpene cyclase genes. To identify the terpenes biosynthesized from H. aurantiacus 114-95T, we fed the strain with 13C-labeled glucose and, subsequently, searched for characteristic mass shifts in its metabolome. This approach led to the discovery of a new natural product, of which the isotope pattern is indicative for a diterpene originating from the methylerythritol phosphate pathway. After large-scale fermentation of H. aurantiacus 114-95T, the putative diterpene was isolated in sufficient quantity to enable NMR-based structure elucidation. The compound, for which the name herpetopanone is proposed, features a rare octahydro-1H-indenyl skeleton. Herpetopanone bears resemblance to cadinane-type sesquiterpenes from plants, but is structurally entirely unprecedented in bacteria. Based on its molecular architecture, a possible biosynthetic pathway is postulated.
Keywords: genome mining; herpetopanone; Herpetosiphon; isotope labeling; terpene